ANALISIS MODAL SOSIAL DALAM PEMBERDAYAAN EKONOMI KELUARGA MISKIN DI KELURAHAN KEDUNG JAYA, KECAMATAN TANAH SAREAL, KOTA BOGOR - Alfiasari Alfiasari (Jurnal Ilmu Keluarga dan Konsumen, 2008)
The importance of social capital in poor family empowerment to increase their level of life is realized by most stakeholders. Some researchers stated that social capital has significant role in increasing family welfare. The aim of this research was to analyze the correlation between social capital and poor family empowerment through “UEK-SP KUBE Gakin” Program was conducted at Kedung Jaya village, Tanah Sareal sub district of Bogor, West Java. This research used cross sectional study as a study design. Sampling frame of this research were poor families which were intervened by “UEK-SP KUBE Gakin” Program. There were 106 poor families getting loan in 1st period and 2nd period during fiscal year 2005 were drawn for this study. This research was conducted for 5 months (Juni until November 2006). Social capital was measured by 3 variables that are trust, networks, and norms. The improvement of family welfare of the “UEK-SP KUBE Gakin” was assessed by measuring of the changing of economic family condition after participated in that program. This research used Spearman Correlation Test to measure correlation between variables. The results showed that social capital had significant correlation with the increasing of poor family economic welfare of “UEK-SP KUBE Gakin” participants. Social capital variables that had significant correlation with the improvement of family welfare of participants were trust (α = 0.01), “UEK-SP KUBE Gakin” rules (α = 0.0), and networks (α = 0.05).